Regulation of the Telomerase Reverse Transcriptase Subunit through Epigenetic Mechanisms - Lewis, Kayla A.; Tollefsbol, Trygve O. (Frontiers in Genetics, 2016)
Chromosome-shortening is characteristic of normal cells, and is known as the end replication problem. Telomerase is the enzyme responsible for extending the ends of the chromosomes in de novo synthesis, and occurs in germ cells as well as most malignant cancers. There are three subunits of telomerase: human telomerase RNA (hTERC), human telomerase associated protein (hTEP1), or dyskerin, and human telomerase reverse transcriptase (hTERT). hTERC and hTEP1 are constitutively expressed, so the enzymatic activity of telomerase is dependent on the transcription of hTERT. DNA methylation, histone methylation, and histone acetylation are basic epigenetic regulations involved in the expression of hTERT. Non-coding RNA can also serve as a form of epigenetic control of hTERT. This epigenetic-based regulation of hTERT is important in providing a mechanism for reversibility of hTERT control in various biological states. These include embryonic down-regulation of hTERT contributing to aging and the upregulation of hTERT playing a critical role in over 90% of cancers. Normal human somatic cells have a nonmethylated/hypomethylated CpG island within the hTERT promoter region, while telomerase-positive cells paradoxically have at least a partially methylated promoter region that is opposite to the normal roles of DNA methylation. Histone acetylation of H3K9 within the promoter region is associated with an open chromatin state such that transcription machinery has the space to form. Histone methylation of hTERT has varied control of the gene, however. Mono- and dimethylation of H3K9 within the promoter region indicate silent euchromatin, while a trimethylated H3K9 enhances gene transcription. Non-coding RNAs can target epigenetic-modifying enzymes, as well as transcription factors involved in the control of hTERT. An epigenetic diet that can affect the epigenome of cancer cells is a recent fascination that has received much attention. By combining portions of this diet with epigenome-altering treatments, it is possible to selectively regulate the epigenetic control of hTERT and its expression.